Checking the pregnancy checkbox: Evaluation of a four‐state quality assurance pilot. Issue 4 (14th March 2019) - Daymude, Anna E. C.; Catalano, Andrea; Goodman, Dave
Abstract: Background: The 2003 revision of the standard United States death certificate included a set of "pregnancy checkboxes" to ascertain whether a woman was pregnant at the time of her death or within the preceding year. Studies validating the pregnancy checkbox have indicated a potentially high number of errors, resulting in inflated maternal mortality rates. In response to concerns about pregnancy checkbox data quality, four state health departments implemented a quality assurance pilot project examining the accuracy of the pregnancy checkbox for 2016 deaths. Methods: State staff conducted searches for birth or fetal death reports that matched a death certificate, within a year of death. If a pregnancy checkbox was marked, but no match was found between certificates, confirmation of the pregnancy was attempted through active follow‐up with the death certifier. From December 2017 to January 2018, the quality assurance pilot was evaluated through three focus groups with key stakeholders. The evaluation aimed to describe opportunities and challenges to implementation, sustainability, and lessons learned. Results: Opportunities for implementing the pilot included written documentation of the quality assurance process, improved certifier response, improved data quality, and increased data timeliness for Maternal Mortality Review Committees. Challenges included initial delays in certifier response, staff turnover, high caseloads in relation to resources, and lack of pilot prioritization in the health department. All four pilot states plan to sustain the pregnancy checkbox quality assurance process in some capacity. Conclusions: Implementing quality assurance processes for the pregnancy checkbox may ultimately improve state and national maternal death data quality.